Production of Tyrian purple indigoid dye from tryptophan in Escherichia coli - Lee, Jeongchan; Kim, Joonwon; Song, Ji Eun; Song, Won Suk; Kim, Eun Jung; Kim, Yun Gon; Jeong, Hee Jin; Kim, Hye Rim; Choi, Kwon Young; Kim, Byung Gee (Nature Chemical Biology, 2021)
Tyrian purple, mainly composed of 6,6'-dibromoindigo (6BrIG), is an ancient dye extracted from sea snails and was recently demonstrated as a biocompatible semiconductor material. However, its synthesis remains limited due to uncharacterized biosynthetic pathways and the difficulty of regiospecific bromination. Here, we introduce an effective 6BrIG production strategy in Escherichia coli using tryptophan 6-halogenase SttH, tryptophanase TnaA and flavin-containing monooxygenase MaFMO. Since tryptophan halogenases are expressed in highly insoluble forms in E. coli, a flavin reductase (Fre) that regenerates FADH2 for the halogenase reaction was used as an N-terminal soluble tag of SttH. A consecutive two-cell reaction system was designed to overproduce regiospecifically brominated precursors of 6BrIG by spatiotemporal separation of bromination and bromotryptophan degradation. These approaches led to 315.0 mg l−1 6BrIG production from tryptophan and successful synthesis of regiospecifically dihalogenated indigos. Furthermore, it was demonstrated that 6BrIG overproducing cells can be directly used as a bacterial dye. [Figure not available: see fulltext.].
Keywords: Biocompatible Materials; Cloning, Molecular; Coloring Agents; Escherichia coli; Escherichia coli Proteins; Flavin-Adenine Dinucleotide; FMN Reductase; Gene Expression; Gene Expression Regulation, Bacterial; Genetic Vectors; Halogenation; Indigo Carmine; Indoles; Metabolic Engineering; Oxidoreductases; Oxygenases; Recombinant Proteins; Semiconductors; Stereoisomerism; Tryptophan; Tryptophanase